Nationalism in Europe, 1815 to the present : a reader - Woolf, S. J. (Stuart Joseph) (Routledge, 1996)
`A major addition to the current literature on the challenging topic of how national identities are moulded.' - Michela Biddiss, Department of History University of Reading.
Keywords: Nationalism.; Nationalism -- Europe.; Nationalisme.; Nationalisme -- Europe.; nationalism.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; Nationalism; Europe